The nature of the bonding in symmetrical pincer palladacycles. Issue 16 (26th March 2015) - Boonseng, Sarote; Roffe, Gavin W.; Spencer, John; Cox, Hazel
Abstract : A method validation, formation reaction via C–H bond activation, and an Atoms in Molecules analysis of symmetrical pincer palladacycles. Abstract : The accuracy of DFT-optimised geometries of the symmetrical pincer palladacycles PdNCN and PdSCS, [ClPd2, 6-(Me2 NCH2 )2 C6 H3 ] and [ClPd2, 6-(MeSCH2 )2 C6 H3 ] respectively, has been evaluated by investigating the performance of eight commonly used density functionals with four combinations of basis set, in reproducing their X-ray crystal structures. It was found that whilst the ωB97XD functional performed best over all, the PBE and TPSS functionals performed best when considering the palladium coordination geometry. The role of the donor atom in the stability and reactivity of the symmetric palladacycles, PdYCY, Y = N, S, or P, has been determined using Bader's Atoms in Molecules method to elucidate the nature of the bonding, and using a model formation reaction, which involves the C–H activation of the pincer ligand YCY by PdCl2 . The calculations reveal distinct differences in the bond strength and nature of the interaction of Pd with the donor atoms Y, which support differences in the thermodynamic stability of the palladacycles.